The Effect of Using Flipped Classroom Strategy via Facebook on Achievement and Attitude toward Mathematics among Seventh Grade Female Students in Gaza - Alashqar, Ayman (Dirasat: Educational Sciences, 2022)
Objectives: This research aims to study the effect of using flipped classroom strategy through Facebook on the achievement and attitude towards mathematics among seventh grade female students in Gaza. The total sample consisted of (85) female students, including an experimental group (n=41) that was taught using the flipped classroom strategy through Facebook, and a control group (n=44) that was taught in the traditional method. Methods: The researcher used a quasi-experimental approach, and a guide for teachers, an achievement test in the unit of engineering and measurement, and a scale for the female students' attitudes towards mathematics were prepared. The validity and reliability of the test and scale were verified, The tests were applied before and after on the two study groups. Results: The study found that there are statistically significant differences at the level of (α=0.05) between the mean achievement and attitudes of the experimental group and control group students in favor of the experimental group. Conclusions: The study recommends the necessity of employing flipped classroom strategy because it has proven to be one of the effective strategies in teaching mathematics to primary school students.